Analysis of Islamic Law (Urf) on Marriage Traditions in Kenteng Village, Bandungan Sub-District, Semarang District - Afi Fathma Syamnik (Pusat Studi Penelitian dan Evaluasi Pembelajaran, 2023)
This research is motivated by the community of Kenteng Village where they often carry out traditions in marriage in the form of pre-mantu stage, mantu stage and post-mantu stage. This is sometimes unique, although sometimes the organisers are overwhelmed. Kenteng Village, Bandungan Subdistrict, still tries to uphold Javanese cultural values in the wedding procession. The purpose of this scientific essay is to explore and examine the nature of the wedding procession based on factual events held in Kenteng Village, Bandungan Subdistrict, Semarang Regency and to examine the phenomenon based on urf review. The research methods used are fieldwork, observation, and interviews. The results of this study indicate that the marriage tradition in Kenteng Village from an urf perspective is permissible because it is considered a wedding gift from the groom's party to the bride's party and does not conflict with Islamic law. Therefore, the marriage tradition should be maintained, because there are positive values that are in line with Islamic teachings, namely in the form of helping, a symbol of a woman's obedience to her husband as the head of the household.